Oxygen-enriched electrolytes based on perfluorochemicals for high-capacity lithium–oxygen batteries1. Issue 20 (28th May 2015) - Nishikami, Yuki; Konishi, Toshihiro; Omoda, Ryo; Aihara, Yuichi; Oyaizu, Kenichi; Nishide, Hiroyuki
<x xml:space="preserve">Abstract</x> Enhanced discharging capacity of a Li–O2 cell was accomplished by using an electrolyte containing high amounts of dissolved oxygen composed of perfluorochemicals (PFCs).